Public green spaces and positive mental health – investigating the relationship between access, quantity and types of parks and mental wellbeing. (November 2017) - Wood, Lisa; Hooper, Paula; Foster, Sarah; Bull, Fiona
Abstract: Associations between parks and mental health have typically been investigated in relation to the presence or absence of mental illness. This study uses a validated measure of positive mental health and data from RESIDential Environments (RESIDE) Project to investigate the association between the presence, amount and attributes of public green space in new greenfield neighbourhood developments and the mental health of local residents (n = 492). Both the overall number and total area of public green spaces were significantly associated with greater mental wellbeing, and findings support a dose-response relationship. Positive mental health was not only associated with parks with a nature focus, but also with green spaces characterised by recreational and sporting activity. The study demonstrates that adequate provision of public green space in local neighbourhoods and within walking distance is important for positive mental health. Highlights: Considered benefits of parks for positive mental health, instead of mental illness. Positive mental health increased with more parks in walking distance to home. Range of park sizes related to positive mental health, including small pocket parks. Parks with varying foci (recreation, nature, sport) all associated with mental health.